Affective disorders and anxiety disorders predict the risk of drug harmful use and dependence - Liang, Wenbin; Chikritzhs, Tanya; Lenton, Simon (Wiley-Blackwell Publishing Ltd., 2011)
Aim: To investigate whether affective disorders, anxiety disorders, and alcohol use disorders may increase the risk of subsequently developing drug (non-alcohol related) dependence and/or drug (non-alcohol related) harmful use. Design: A retrospective cohort study based on nationally representative household survey data collected from the 2007 National Survey of Mental Health and Wellbeing (MHW). The MHW survey applied the World Mental Health Survey Initiative version of the Composite International Diagnostic Interview (WMH-CIDI 3.0) to collect information on ICD-10 mental disorder diagnoses. Ages at first onset for mental disorders and harmful drug use were used to reconstruct the cohort according to: definition of exposure, time at risk and outcome. Participants: 8,841 Australian adults aged 18-85 yrs who were included in the 2007 MHW survey. Findings: Participants with affective disorders and anxiety disorders were at higher risk of drug harmful use and drug dependence and the effects did not vary by the length of time respondents had been exposed to mental disorders.Conclusion: It is uncertain whether experience of affective disorders and anxiety disorders, possibly prior to the disorder being identified by the individual or a health worker, may lead to self medication with psychoactive substances or whether common genetic factors linking mental disorder and drug use disorders are the underlying cause. Symptoms of mental health disorders should alert health care providers to the possibility of drug use disorder co-morbidity and the need for early intervention, especially among young males.